The folklore in everyday life of Education Child - Ana Karina Corrêa; Maria Patrícia Soares da Silva (Universidade Federal de Santa Catarina, 2009)
The fact file of our day to day with the children of the group contributed 6B significantly to dedicássemos a closer look carefully for them and for their multiple languages, for their tastes, their cultural repertoire and one thousand forms of expression and creation. Taken together, these observations allowed us to build a proposal seeking socio include the information of his children, without losing sight of the work that was already being developed by the group and teacher the goals of our internship.